Financial inclusion: New measurement and cross-country impact assessment - Cyn-Young Park; Rogelio V. Mercado (Asian Development Bank (ADB), 2018)
This paper introduces a new index of financial inclusion for 151 economies using principal component analysis to compute weights for aggregating nine indicators of access, availability, and usage. It then assesses the impact of financial inclusion on poverty and income inequality. The results provide evidence that high- and middle-high-income economies with high financial inclusion have significantly lower poverty, while no such relation exists for middle-low and low-income economies. The nonlinearities in the cross-country determinants and impacts of financial inclusion on poverty and income inequality across income groups are important to choosing the appropriate policies for achieving inclusive growth in different development stages.
Keywords: G18; O11; O16; 330; financial inclusion; income inequality; poverty